The digital ordinary: Digitalization of everyday life as a form of labour - Lasén Díaz, Amparo (Cuadernos de Relaciones Laborales, 2019)
This paper discusses some aspects of the digital ordinary: the growing digitalization of our everyday life with the pervasiveness of digital practices and the production and storage of digital inscriptions about our ordinary life, relationships, affects, opinions and activities, that become the content of platforms, apps and search engines, as well as the matter the so called big data are made of, whose commodification constitutes the gain source or business model of the corporations owning these platforms and apps. The sociability and forms of self(re)presentation digitally enacted present ethic and aesthetic particularities; and entail forms of contemporary digital labour, face work and affective work, subject to reflexivity, surveillance and control, which are described and discussed drawing on research about the production and sharing of digital images, such as selfies.